Googling and health anxiety in older age—A case study of CBT incorporating a single case experimental design - Hill, S; Watts, D (Wiley Open Access, 2024)
Key Clinical Message: The use of online search engines to “google” health‐related information is common in health anxiety, and requires careful consideration within psychological treatment. Its nature in older adult populations is less closely understood. This report demonstrates the reduction in googling frequency using cognitive‐behavioral therapy in an 83‐year‐old female with health anxiety.